Microbiological and Clinical Characteristics of Bloodstream Infections in General Intensive Care Unit: A Retrospective Study - Wu, He-Ning; Yuan, Er-Yan; Li, Wen-Bin; Peng, Min; Zhang, Qing-Yu; Xie, Ke-liang (Frontiers in Medicine, 2022)
Background: Bloodstream infections (BSI) are one of the common causes of morbidity and mortality in hospitals; however, the pathogenic spectrum and bacterial antibiotic resistance vary across the world. Therefore, identifying the pathogenic spectrum and changes in bacterial antibiotic resistance is critical in controlling BSI and preventing the irrational use of antibiotics. Methods: This study retrospectively analyzed the distribution and antibiotic resistance of pathogens based on the clinical data of BSI patients presented in the ICU from 2018 to 2020. Test performance for the prediction of pathogen species was assessed by receiver operating characteristic (ROC) analysis. Results: The analysis of the data of 382 BSI cases (10.40 cases per thousand patient day) revealed the most frequently isolated microorganisms to be Klebsiella pneumonia (11.52%), followed by Escherichia coli (9.95%), Staphylococccus epidermidis (9.95%), Candida parapsilosis (8.12%), and Enterococcus faecium (8.12%). Out of the isolated E. coli and K. pneumonia strains, 52.63% and 36.36%, respectively, were extended-spectrum β-lactamase (ESBL) positive. Among the isolated 55 fungal strains, C. parapsilosis was the most common one (30/55, 56.36%). Except for the cases with two or more strains in the same culture medium, compared with the patients with Gram-positive and fungal pathogens, patients with Gram-negative bacteria exhibited the highest sequential organ failure assessment (SOFA) score (P < 0.001), lowest Glasgow Coma Scale (GCS) (P = 0.010), lowest platelet (PLT) value (P <0.001), highest plasma creatinine (Cr) value (P = 0.016), and the highest procalcitonin (PCT) value (P <0.001). The area under the curve (AUC) in the ROC analysis for the differentiation of Gram-negative BSI from Gram-positive and fungal BSI by PCT was 0.7 (95% confidence interval [CI], 0.644–0.755), with a cutoff value of 16.62 ng/mL (sensitivity 57.5% and specificity 74%). Conclusions: A wide range of pathogens was detected in BSI patients, especially the older ones, and varying antibiotic-resistance rates were observed for the isolated strains. Therefore, antibiotics should be used reasonably according to the distribution and antibiotic resistance of pathogens in different BSI patients. Moreover, PCT may be used as a test index to distinguish Gram-negative BSI from Gram-positive BSI and fungal BSI.